T90. QUANTIFYING THE CORE DEFICIT IN CLASSICAL SCHIZOPHRENIA. (18th May 2020) - Rathnaiah, Mohanbabu; Liddle, Elizabeth; Gascoyne, Lauren; Kumar, Jyothika; Katshu, Mohammad; Faruqi, Catherine; Kelly, Christina; Gill, Malkeet; Robson, Sian; Brookes, Mathew; Palaniyappan, Lena; Morris, Peter; et al.
Abstract: Background: For more than 100 years, disorganization and impoverishment of mental activity have been recognised as fundamental symptoms of schizophrenia. These symptoms may reflect a core brain process underlying persisting disability. Predisposition to persisting disability is a clinically important aspect of schizophrenia, yet the psychopathological processes predisposing to persisting disability are poorly understood. The delineation of a putative core deficit associated with persisting disability would be of potentially great value in delineating the underlying pathological processes and eventually in enhancing treatment. Aims: To derive scores for mental disorganization and impoverishment from commonly used rating scales, and test the hypothesis that disorganization and impoverishment, along with impaired cognition and role-function reflect a latent variable that is a plausible candidate for the putative core deficit. Methods: In a group of 40 patients with schizophrenia, we tested the hypothesis that mental disorganization and impoverishment, along with impaired cognition and role-function reflect a latent variable that is a plausible candidate for the core deficit. We derived disorganization and impoverishment factors from three symptom scales: PANSS, SSPI and CASH. For each of the three scales, we demonstrated significant correlation between these factors and impaired role function assessed using the Social and Occupational Functioning Scale (SOFAS) and cognitive impairment measured using the Digit Symbol Substitution Test (DSST). We then assessed the relationship between this latent "core deficit" variable and Post Movement Beta Rebound (PMBR), measured using magnetoencephalography and associated with persisting brain disorders. Results: A single factor model provided excellent fit for the four features of core deficit, requiring no further modifications. Results were consistently similar for measures from all three scales. χ2 value was non-significant (range: 0.30 to 2.13, df = 2, p > 0.35), GFI met the threshold of greater than 0.9 (range = .976 to .996) and RMSEA was lesser than 0.06 (range = 0.000 to 0.040). PMBR was found to be significantly reduced in the schizophrenia group compared to healthy controls (t (28) =44.2 ± 12.1, p = 0.001). PMBR was strongly correlated with disorganization (r (40) = .600, p=0.001). In the hierarchical regression, neither age nor medication dose were significant predictors, but PMBR did predict the severity of the core deficit (F (1, 23) = 12.6, P=0.002, R² = -.592). Discussion: Scores for the two latent variables representing impoverishment and disorganization of mental activity in schizophrenia can be derived from each of three symptom rating scales. A composite measure of impoverishment, disorganization, impaired cognition and impaired role function reflects an underlying psychopathological process that might be described as the core deficit of classical schizophrenia.